PENGARUH KEPEMIMPINAN MANAJER TERHADAP KEPUASAN KERJA KARYAWAN DI NEW D’DHAVE HOTEL PADANG - Rizqi, Afdhal; Kasmita, Kasmita; Ferdian, Feri (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research started from the results of pre-research observations ofemployees of New d'Dhave Hotel Padang who complained about their leaders. Thisstudy aims to analyze the Effect of Manager Leadership on Job SatisfactionEmployees at New d'Dhave Hotel Padang. The type of this research is descriptivequantitative with causal assosiative method. The number of samples in this studyamounted to 30 people taken using the technique of saturated sampling. Datacollection technique is done by questionnaire by using Likert scale that has beentested the validity and reliability. Based on the research that has been done thenobtained the results of simple linear regression hypothesis test obtained a constantvalue (a) of 71,831, this figure has meaning if there is no managerial leadership (X)then the value of consistent job satisfaction (Y) is 71.831. Then obtained the value ofregression coefficient (b) of -0.420, this figure means that every increase of 1 unit ofmanagerial leadership (X), then job satisfaction (Y) will decrease by -0.420. thenobtained R square equal to 0,137, namely an effect of 13,7%.